Prispevek k poznavanju postranic iz skupine Gammaridea (Amphipoda, Gammaridea) slovenske morske obale - Fišer, Cene (Natura Sloveniae, 2002)
Among 46 amphipod species found along slovenian sea-coast, Microdeutopus sporadhi, Microdeutopus obtusatus, Gammarus subtypicus and Orchestia stephenseni were recorded for the first time in the northern Adriatic.
Keywords: Amphipoda; Crustacea; Gulf of Trieste; Morska voda; postranice; Seawater; Tržaški zaliv